Contrasting effect of Saharan dust and UVR on autotrophic picoplankton in nearshore versus offshore waters of Mediterranean Sea. Issue 8 (19th August 2017) - González‐Olalla, J. M.; Medina‐Sánchez, J. M.; Cabrerizo, M. J.; Villar‐Argáiz, Manuel; Sánchez‐Castillo, Pedro M.; Carrillo, Presentación
Abstract: Autotrophic picoplankton (APP) is responsible for the vast majority of primary production in oligotrophic marine areas, such as the Alboran Sea. The increase in atmospheric dust deposition (e.g., from Sahara Desert) associated with global warming, together with the high UV radiation (UVR) on these ecosystems, may generate effects on APP hitherto unknown. We performed an observational study across the Alboran Sea to establish which factors control the abundance and distribution of APP, and we made a microcosm experiment in two distinct areas, nearshore and offshore, to predict the joint UVR × dust impact on APP at midterm scales. Our observational study showed that temperature ( T ) was the main factor explaining the APP distribution whereas total dissolved nitrogen positively correlated with APP abundance. Our experimental study revealed that Saharan dust inputs reduced or inverted the UVR damage on the photosynthetic quantum yield (ΦPSII ) and picoplanktonic primary production (PPP ) in the nearshore area but accentuated it in the offshore. This contrasting effect is partially explained by the nonphotochemical quenching, acting as a photorepair mechanism. Picoeukaryotes reflected the observed effects on the physiological and metabolic variables, and Synechococcus was the only picoprokaryotic group that showed a positive response under UVR × dust conditions. Our study highlights a dual sensitivity of nearshore versus offshore picoplankton to dust inputs and UVR fluxes, just at the time in which these two global‐change factors show their highest intensities and may recreate a potential future response of the microbial food web under global‐change conditions. Key Points: Aerosol deposition over the past 35 years reveals an increasing trend in the mean intensity of these events over Alboran Sea Nearshore autotrophic picoplankton is more sensitive to UVR impact than those from offshore UVR × dust exerted a positive effect on autotrophic picoplankton in nearshore but negative in offshore